SARS-CoV-2 spike protein induces the cytokine release syndrome by stimulating T cells to produce more IL-2 - Niu, Chao; Liang, Tingting; Chen, Yongchong; Zhu, Shan; Zhou, Lei; Chen, Naifei; Qian, Lei; Wang, Yufeng; Li, Min; Zhou, Xin; Cui, Jiuwei (Frontiers in Immunology, 2024)
Cytokine release syndrome (CRS) is one of the leading causes of mortality in COVID-19 patients caused by the SARS-CoV-2 coronavirus. However, the mechanism of CRS induced by SARS-CoV-2 is vague. This study shows that dendritic cells loaded with spike protein of SARS-CoV-2 stimulate T cells to release much more IL-2, which subsequently cooperates with spike protein to facilitate peripheral blood mononuclear cells to release IL-1β, IL-6, and IL-8. These effects are achieved via IL-2 stimulation of NK cells to release TNF-α and IFN-γ, as well as T cells to release IFN-γ. Mechanistically, IFN-γ and TNF-α enhance the transcription of CD40, and the interaction of CD40 and its ligand stabilizes the membrane expression of TLR4 which serves as a receptor of spike protein on the surface of monocytes. As a result, there is a constant interaction between spike protein and TLR4, leading to continuous activation of NF-κB. Furthermore, TNF-α also activates NF-κB signaling in monocytes, which further cooperates with IFN-γ and spike protein to modulate NF-κB-dependent transcription of CRS-related inflammatory cytokines. Targeting TNF-α/IFN-γ in combination with TLR4 may represent a promising therapeutic approach for alleviating CRS in individuals with COVID-19.